The gamut of clinical manifestations - Mendes, Rinaldo Poncio [UNESP] (Taylor & Francis, 2018)
Paracoccidioidomycosis is a systemic disease that presents marked tendency toward dissemination with involvement of any organ or system. In order to illustrate the most frequent and also some of the uncommon clinical presentations, case histories of patients withparacoccidioidomycosis are reported. The importance of cutaneous involvement in paracoccidioidomycosis is related to its frequency, the possibility it provides for an easy diagnosis and often, to the exuberance of the lesions. The skin is reached by the fungus either by hematogenic dissemintion or by contiguity from mucosal or lymph node lesions. The high incidence of adrenal lesions in paracoccidioidomycosis was then characterized; these glands occupy the third place among the viscera involved. Information about the participation of bones and joints in paracoccidioidomycosis has been obtained from reports of isolated cases or of small series. Urogenital involvement in paracoccidioidomycosis usually occurs in patients with lesions of other organs, the lungs in particular; it is almost exclusively encountered in males.